The browser hacker's guide to instantly loading everything (O'Reilly Media, 2017)
"Venture deep into the belly of the browser to uncover the secret to instantly loading anything--backed by data. Addy Osmani explains how to use preload, prefetch, preconnect, HTTP/2 server push, service workers, and more and how to ship JavaScript bundles on mobile that don't break the bank as he shares data-driven techniques and performance patterns for efficiently loading content instantly."--Resource description page